The Role of Creative Economic Growth, Production Value, and Investment in Labor Absorption in East Lombok Regency - Sari, Nurmala; Ismiwati, Baiq (West Science Social and Humanities Studies, 2024)
The growth of the creative economy in East Lombok Regency offers great potential to create jobs and increase local competitiveness. The production value in this sector is an important indicator to measure the contribution of the creative economy to the economy, while investment plays a crucial role in driving innovation and production capacity. This study aims to analyze the effect of creative economic growth, production value, and investment on labor absorption in East Lombok Regency. This type of research is quantitative descriptive using secondary data. The results of the analysis of this study indicate that the growth of the creative economy has a fairly large role in labor absorption in East Lombok Regency. This is indicated by the results of the regression calculation which gives the result that the growth of the creative economy has a significant effect on labor absorption. However, the production value and investment do not show a significant effect on the welfare of workers in the area. However, the increase in production value is expected to support the growth of the creative economy sector. Overall, the results of simultaneous calculations show that the growth of the creative economy has a significant role in labor absorption in East Lombok Regency. On the other hand, although the production value and investment do not show a significant direct effect, they are still important supporting factors in the development of the creative economy.